First study on the outcomes of biliopancreatic diversion with duodenal switch in Chinese patients with obesity - Wang, Lun; Zhang, Zheng; Wang, Zeyu; Jiang, Tao (Frontiers in Surgery, 2023)
Background Biliopancreatic diversion with duodenal switch (BPD-DS) is a bariatric procedure used in the treatment of obesity and related metabolic disorders.However,to date,the data on BPD-DS among Chinese patients with obesity is completely lacking. Objective This is the first study to evaluate the safety and efficacy of BPD-DS in the treatment of Chinese patients with obesity. Methods Data from twelve patients undergoing BPD-DS between September 2019 and March 2020 were analyzed retrospectively to evaluate complications, weight loss,comorbidity resolution and nutritional status. Results All patients completed the 1-year follow-up.There was no conversion to laparotomy or death.Mean operative time was 257.08±29.27 minutes.Median length of stay was 7 days (range 4–38 days).Complications occurred in 3 patients.The 1-year body mass index (BMI) was 25.13±4.71 kg/m2 with a mean excess weight loss of 100.11±33.29% and a mean total weight loss of 43.22±7.71%.Remission was achieved in 100% (7/7 cases) for type 2 diabetes,in 83.3% (10/12 cases) for hypertension, and in 62.5% (5/8 cases) for hyperuricemia. At 1 year after BPD-DS,the prevalence of albumin deficiency was 16.7%,iron deficiency 16.7%, and zinc deficiency 50%. 8.3% of the patients were anaemic.High deficiency rates for vitamins were presented mainly in vitamin A and vitamin E:vitamin A in 58.3 % and vitamin E in 50 % of the patients.The prevalence of asymptomatic gallstones increased significantly from preoperative 0% to postoperative 41.7%. Conclusion BPD-DS had excellent weight loss and resolution of comorbidities among Chinese patients with obesity.However,high rates of nutritional deficiencies and complications were found after BPD-DS, especially for vitamin A and vitamin E.